Freud and the Post-Freudians - Brown J.A.C (Penguin Books, 1983)
Freud revolutionized the way we look at ourselves. Basics Concepts of Psychoanalysis, The Theories of Freud: A General Survey, The Early Schismatics, The British Schools, The Psychosomatic Approach, Psychoanalysis and Society, The Theories of Karen Horney, The Theories of Erich Fromm, Harry Stack Sullivan and Others, Assessments and Applications, Bibliography, Index.